How do pre-service teachers integrate knowledge when reflecting on a pedagogical situation? An analysis of concept maps in teacher education - Molitor, Anna-Lena; Schellenbach-Zell, Judith; Hartmann, Ulrike (Frontiers in Education, 2025)
The use of professional knowledge (from different areas; content knowledge, pedagogical knowledge, pedagogical-psychological knowledge)—that is, scientific evidence in the broader sense—can help teachers to act professionally in complex pedagogical situations. An important part of the professional use of evidence is the integration of various components of knowledge. Existing research evaluates knowledge integration dichotomously or refers to multiple document research, although we assume that the structures are more complex and should be taken into account when promoting knowledge integration of prospective teachers. Concept maps—that represent mental structures—enable a detailed assessment of structures of integrated knowledge. The aim of this study is to work out differentiated structures of knowledge integration. In a field setting, 33 master’s students (primary science education) designed concept maps to analyze a given pedagogical situation. The maps were coded structurally and thematically. Additionally, graph theoretical measures were applied. Results show three types of knowledge integration that we call Interrelation, Side-by-Side Integration and Merging. We discuss these types in terms of theoretical implications and possible benefits for teacher education. A differentiated analysis of structures of knowledge integration can be used to create individualized learning opportunities.